Rising star : China's new security diplomacy - Gill, Bates (Brookings Institution Press, 2010)
China's diplomatic strategy has changed dramatically since the mid-1990s, creating both challenges and opportunities for other world powers. Through a combination of pragmatic security policies, growing economic clout, and increasingly deft diplomacy, China has established productive and increasingly solid relationships throughout Asia and around the globe. Yet U.S. policymakers are still trying to comprehend these critical changes. Rising Star provides a coherent framework for understanding China's new security diplomacy and guiding America's China policy. Bates Gill has completely updated his original analysis, focusing on Chinese policy in three areas: regional security mechanisms, nonproliferation and arms control, and questions of sovereignty and intervention. Looking to the future, he offers specific recommendations for a balanced and realistic approach that emphasizes what China and the United States have in common, rather than what divides them. The main arguments and recommendations of the original book continue to hold true and, in many respects, are more compelling now than ever before given China's continued ascendancy -- publisher's web site.